2015
DOI: 10.1007/s10209-015-0418-z
|View full text |Cite
|
Sign up to set email alerts
|

Increasing participation in the information society by people with disabilities and their families in lower-income countries using mainstream technologies

Abstract: Assistive technology (AT) has been actively researched, developed and implemented throughout higher-income countries, but is relatively absent from lowerincome countries. In lower-income countries, there is very little AT for reading, writing, communicating and for participation in the information society. In order for persons with disabilities in lower-income countries to participate fully in society, mainstream Information and Communication Technologies (ICTs) such as mobile phones should be used as AT. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 33 publications
2
7
0
Order By: Relevance
“…The latter eight participants all had access to Internet-connected ICTs. Participants in our study had relatively high mobile phone use (70% of participants) and lower computer use (40% of participants), in-line with current ICT trends, including increased use of mobile connected devices and smartphones and the decline of desktop computer use, as noted by Barlott et al (2016). Although not discussed directly with participants, the steering committee noted that people with ID who attend their adult literacy program want to use mainstream ICTs, they want to ‘use devices that everyone else is using’.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The latter eight participants all had access to Internet-connected ICTs. Participants in our study had relatively high mobile phone use (70% of participants) and lower computer use (40% of participants), in-line with current ICT trends, including increased use of mobile connected devices and smartphones and the decline of desktop computer use, as noted by Barlott et al (2016). Although not discussed directly with participants, the steering committee noted that people with ID who attend their adult literacy program want to use mainstream ICTs, they want to ‘use devices that everyone else is using’.…”
Section: Discussionsupporting
confidence: 78%
“…ICTs include any electronic technology that provides the means to access information or facilitate communication and may include physical technology such as mobile phones and computers or non-physical technology such as the Internet and online social networks (Barlott et al, 2016). Previous studies within the general adult population show promising results for the use of ICTs and social connectedness, with a number of studies finding that the use of ICTs can help maintain relationships (Chayko, 2014), increase social interaction with others (Chayko, 2014, Satici et al, 2016) and create a sense of belonging and relatedness (van Bel et al, 2009).…”
mentioning
confidence: 99%
“…The improved social connection demonstrated by this research is in line with other evidence that mobile phone devices can improve access to information, promote local knowledge, as well as facilitate sharing and improving social interaction for marginalised populations such as persons with disabilities [16]. Though not specific to mobile technology studies in China have shown internet connection significantly reduces social barriers for disabled people [17], and others in Peru, Jordan and India have shown technology use can improve social and economic aspirations [18].…”
Section: A Social Connectionsupporting
confidence: 84%
“…In many cases, mobile technology is the preferred platform for inclusion projects due to widespread familiarity and availability in low-and middle-income countries (LMICs). Such devices can improve access to information and promote interaction for vulnerable populations, including those with disabilities (Barlott, Adams & Cook 2016) [5]. If this opportunity is to be realised, devices must combine affordability with accessibility and usability.…”
Section: 1mentioning
confidence: 99%